Politics 3: The Fight of University under Conditions of Democracy - Kačerauskas, Tomas; Zavadskas, Edmundas Kazimieras (Problemos, 2006)
The article deals with pluralistic society whose analysis is based on the case of the university as a democratic institute. The authors substantiate three theses. The major one states that the biggest advantage of democracy (freedom of thought) leads to the fight and involves its biggest disadvantage – violence. According to the minor (second) thesis, university as part of democratic society embraces not only the freedom of thought, but also fight. The third thesis says that democracy is constituted “from below”. This insight is used as a point of departure to substantiate the first two theses.
Keywords: democracy; fight; violence; university; politics